Uji Aktivitas Antibakteri Ekstrak Etanol 70%, Etanol 96%, dan Metanol Daun Kelakai Merah (Stenochlaena palustris (Burm.F) Bedd) terhadap Bakteri Cutibacterium acne - Fitri Yanti; Malik Yustika; Setyo Yogi; Azwarina Nuke; Rusida Esty Restiana; Vebruati Vebruati; Hidayati Rahmi (Politeknik Kaltara, 2023)
Acne is an inflammation or infection of the pilosebaceous tract with the bacterium Cutibacterium acne. Lalakai or kelakai plant (S.palustris (Burm.F) Bedd) includes plants that have antibacterial activity. This study aimed to determine the yield and phytochemical compound contained in extracts of 70% ethanol, 96% ethanol, and methanol of the leaves of the (S.palustris Burm.F) Bedd) against Cutibacterium acne bacteria. The method of antibacterial activity was carried out using the good diffusion method. Tests with 6 groups of extract concentrations, namely 100%, 75%, 50%; 37.5%, 25%; and 12.5%. The phytochemical compounds test identified alkaloids, flavonoids, tannins, steroids/triterpenoids, and saponins. The highest extract yield was from 70% ethanol extract of 6.3559%. The results of the phytochemical compound showed that the 70% ethanol, 96% ethanol, and methanol extracts of the leaves Kelakai (S.palustris (Burm.F) Bedd) positively contained alkaloids, flavonoids, tannins, steroids, and saponins. The best antibacterial test came from the methanol extract (concentration of 100%) was able to inhibit C. acne with 14.475 mm (an inhibition zone diameter) which was included in the strong category.